The interpretation of cultural and historical objects as a problem of hermeneutical understanding - Zhilyakov, Sergei V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The article proposes a method review of cultural and historical objects interpretation in the framework of the hermeneutical approach. It uncovered two diametrically opposite comprehension strategies: an objective judgment that demand minimum intervention in the research object for all the impossibility of „impersonal” its study and personal orientation of researching view, allowing a minimum subject’s presence of the study with maximum preservation of its autonomy and independence. The conclusion of the dialectical addition of these two principles in the normal state of the research process is making. An important emphasis is placed on the isolation of the object by cultural and historical context, while nondisturbing its natural connection with it (horizon comprehension). methodological recommendations are leading to the most complete and reliable understanding of the cultural and historical objects into the focus of the start interpretive dominance within hermeneutical studies.